Effect of Container Type and Size on Growth Performance and Quality Parameters of Juniperus polycarpos C. Koch Seedlings Under Nursery Condition - Negi, P. S.; Sharma, Sandeep; Thakur, Neha (Indian Forester, 2023)
A trial was conducted to study the effect of different container type and size on the seedling growth performance and quality parameters of Juniperus polycarpos under nursery condition. One year old seedlings of J. polycarpos raised in germination beds were transplanted in different containers filled with potting media having eight treatments with five replications in randomized block design. Significant differences were observed in shoot length, collar diameter, root length, number of roots and root and shoot biomass of Juniperus polycarpos seedlings raised in different containers including nursery beds. Maximum values of various seedling parameters viz., shoot length (55.17 cm), collar diameter (7.43 mm), root length (49.93 cm), number of roots (46.26) were recorded in seedlings raised in polybags (25 cm x 15 cm) where as minimum values of various seedling parameters were recorded in seedlings raised in Root trainers 150cc Hiko Pots. Maximum values of fresh shoot biomass (41.48 g seedling-1), fresh root biomass (10.09 g seedling-1) and total fresh biomass (51.58g seedling-1) were recorded in seedlings raised in polybags (25cm x 15 cm) whereas minimum values of fresh shoot biomass (5.01 g seedling-1), fresh root biomass (1.90 g seedling-1) and total fresh biomass (6.92g seedling-1) were recorded in seedlings raised in Root trainers 150cc Hiko Pots. Similarly, maximum values of dry shoot biomass (20.07 g seedling-1), dry root biomass (8.38 g seedling-1) and total dry biomass (28.45g seedling-1) were also recorded in seedlings raised in polybags (25 cm x 15 cm) whereas minimum values of dry shoot biomass (2.45 g seedling-1), dry root biomass (0.57 g seedling-1) and total dry biomass (3.08 g seedling-1) were recorded in seedlings raised in Root trainers 150cc Hiko Pots. The maximum values of root shoot ratio (0.42), volume index (3045.65) and quality index (2.90) were also recorded in seedlings raised in polybags (25 cm x 15 cm) followed by seedlings raised in polybags (23 cm x 13 cm), however, least value of sturdiness quotient (5.99) was observed in seedlings raised in Root trainers 300cc Hiko Pots. The results of the study recommend that seedlings of Juniperus polycarpos should be raised in polybags of size 25 cm x 15 cm for production of quality nursery stock.